Implementation of Information Technology at The Amil Zakat Institution LAZiS Central Java-Pekalongan Service Office - Novalini Jailani; Azam Rivani; AM. Muh. Khafidz Ma’shum (Velocity: Journal of Sharia Finance and Banking, 2022)
This study aims to describe the implementation of information technology at the amil zakat institution, LAZiS Central Java, Pekalongan Service Office. This research was conducted by field research with a descriptive qualitative approach to describe the information technology used in inputting and presenting financial information in zakat management at LAZiS Central Java, Pekalongan Service Office. Primary data sources were obtained from direct interviews with financial staff and leaders of LAZiS Central Java Pekalongan service office who knew about website application and financial management and zakat utilization. Secondary data were obtained from various books, articles, journals and authoritative websites relevant to this research. Data collection is done through observations in the use of the web by paying attention to several menus and web appearances. The results of this study found that LAZiS Central Java had used information technology in managing zakat funds that had been collected. This institution uses web-based information technology, namely silazisku.org. This system can only be used by internal institutions, namely the finance department. The process of recording history and presenting financial information becomes more efficient, fast and neat, making it easier for institutions to present financial reports to facilitate audits by using Silazisku.org,. The risks faced by Central Java LAZiS are more manageable than before. The implementation of the zakat information technology system at this institution was able to facilitate managers in managing zakat and provide extensive information to the public about the ease with which people pay zakat